Schottky Contact of Gallium on p-Type Silicon - B.P. Modi; K.D. Patel (Журнал нано- та електронної фізики)
The evolution of barrier at Schottky contact and its stabilization to value characterized by the barrier height and unambiguous measurement is still being curiously perused as they hold the key control and manufacture of tailor made Schottky devices for a host of existing and potential for future applications in electronics, optoelectronics and microwave devices. In this context, gallium – silicon Schottky diode has been fabricated and analyzed.